Comparison of Effectiveness and Complication Rate in Patients of Acute Ischemic Stroke Undergoing Early Vs Delayed Stent Retrieval Mechanical Thrombectomy - Rehman, Mehar; Jahanzeb Liaqat; Faheem ur Rehman; Uzair Ijaz Malik; Atta Gillani (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare effectiveness and rate of complications in patients with acute ischemic stroke undergoing early (within 4.5 hours) vs delayed (4.5-12 hours) mechanical thrombectomy. Study Design: Quasi-Experimental Study. Place & Duration of Study: PEMH, Rawalpindi, Pakistan, from Jan to Sept 2025. Methodology: 100 patients were selected from Neurology OPD / ER PEMH Rawalpindi who presented with Acute Ischemic Stroke. After written informed consent, they were divided into early (onset of CVA < 4.5 hours) or delayed (onset of CVA 4.5-12 hours) group. National Institute of Health Stroke Score (NIHSS) and modified Rankin Score (MRS) were calculated at this time, and basic bio data (age, gender, diabetes, hypertension, ischemic heart disease status, and previous CVA) were documented. Patients then underwent stent retrieval and mechanical thrombectomy and were prospectively observed for complications (Bleeding, Reperfusion Injury & stroke recurrence) and duration of hospital stay. NIHSS was calculated at discharge and MRS at discharge and at 03 months follow-up. All data were analyzed using SPSS Version 25. Results: There was significant improvement in MRS at 03 months in the early vs. Delayed-Group (80% vs 43.3%) (p-value 0.0005), but not in NIHSS at discharge (p-value 0.615). Median (IQR) hospital stay was shorter in the early vs delayed group, 5 (3) days vs 6 (3) days, (p-value < 0.001). Conclusion: The early intervention group showed better MRS scores at 03 months and shorter hospital stay than the delayed group.